Analisis Strategi Bersaing PT. Dewa Arystama Tour & Travel Dolopo Madiun di Tengah Persaingan Usaha Jasa Travel Online - Anisa Maya Umri Hayati; Faruq Ahmad Futaqi (Niqosiya: Journal of Economics and Business Research, 2024)
The rapid development of technology has led to the emergence of online-based airplane ticket agents that hurt traditional ticket agents. Therefore, a competitive strategy is needed so that traditional ticket agents can compete with online ticket agents. This study aims to determine the competitive strategy of PT Dewa Arystama Tour & Travel amid competition for online travel services. This type of research is field research using a qualitative research approach. The data used in this study are primary data obtained through interviews and observations at PT Dewa Arystama Tour & Travel. Data collection techniques using interviews and observations. The analysis results in this study are the competitive strategies used by PT Dewa Arystama Tour & travel in the midst of the threat of online travel services: low cost, differentiation, and focus strategies. Implementing these competitive strategies is by Islamic law, including providing honest, trustworthy services and maintaining friendships with consumers. These strategies are implemented with the primary objective of helping and providing comfort for consumers in traveling. The impact of implementing this strategy is to satisfy consumers so that many return to PT Dewa Arystama.